Vietnam : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2021)
Successful containment of COVID-19 and strong policy support have helped contain the health and economic fallout, and a strong recovery is underway. Growth in 2020 reached 2.9 percent, among the highest in the world. However, labor market conditions remain weak. Corporate balance sheets have worsened, potentially hampering private investment and job prospects. Banks entered the crisis in a stronger position than in previous years, but weaknesses remain. Vietnam's economy remains heavily reliant on external trade and is vulnerable to trade tensions.